(untitled) (Acta Polytechnica CTU Proceedings, 2024)
This study explores the potential of using fine recycled aggregate (FRA) to replace natural sand in concrete production. The research was divided into two parts. In the first part, natural aggregate’s complete fine fraction (0‑4 mm) was replaced with FRA in conventional concrete for two strength classes. In the second part, individual fine components of high-performance concrete (HPC) were substituted with a similar fraction of fine recycled HPC and concrete aggregate. The physical and mechanical properties of these mixtures with recycled aggregate were evaluated against reference mixtures that contained only natural aggregate, following European standards. Results showed that while most of the concrete and HPC mixtures with recycled aggregate showed slight decreases in properties compared to the reference mixes, the most significant reduction in mechanical properties was observed in the flexural tensile strength of the concrete mixture with FRA, which decreased by over 50 %. The absorption by immersion increased by up to 85 %. The deterioration in properties must be considered during the design stage and only used in applications where it will not affect the functionality of the structures.